Investigation of fluctuation in infestation of citrus whitefly Dialeurodes citri (Ashmead, 1885) and its predators in organic citrus orchards under varying climatic conditions: A case study from north-west Algeria - Abdelhaq MAHMOUDI; Leila ALLAL BENFEKIH; Matheus GOOSEN (Acta Agriculturae Slovenica)
The citrus pest, Dialeurodes citri (Ashmead, 1885), poses a significant threat to citrus crops, impacting growth. Various control methods, including biological measures using natural predators like Clitostethus arcuatus (Rossi, 1794), Chrysoperla carnea (Stephens, 1836), and Semidalis aleyrodiformis (Stephens, 1836), were studied over a year in the Chlef region of northwest Algeria. Results indicated that a temperature range of 19.5 °C to 30.5 °C, with 65 % humidity and no precipitation, favored the emergence of D. citri adults. Throughout the study, S. aleyrodiformis and C. arcuatus emerged as the predominant predators. A strong negative correlation (r = -0.91) was observed between D. citri abundance and C. arcuatus caught on traps. The correlation between nymphal infestation rates and monthly average temperatures was negative (r = -0.72), with temperatures ranging from 13 °C to 27 °C and humidity between 47 % and 73 %, conducive to D. citri nymphal infestation. Precipitation negatively impacted D. citri and its predators, causing a decline in adult numbers during the rainy season. The overarching goal is to establish an integrated biological control system, bolstering the economic viability of citrus cultivation in the region.